Onset of Oral Lichen Planus Led to Direct-Acting Antiviral Therapy in a Patient with Long-Term Hepatitis C: The Role of a Dentist as Gatekeeper - Yumiko Nagao; Masahide Tsuji (Case Reports in Gastroenterology, 2023)
Oral lichen planus (OLP), a chronic inflammatory mucocutaneous disease, is an extrahepatic manifestation of a hepatitis C virus infection. In recent years, direct-acting antivirals (DAAs) have made great strides in the treatment of hepatitis C. However, there might be a lack of information about the treatment strategies available among those with this condition. Herein, we report a case of an 85-year-old female patient who was diagnosed with hepatitis C at the age of 55 but had not received antiviral treatment over the past 30 years. She underwent DAA treatment following a recommendation from her oral surgeon after the onset of OLP. The patient had declined interferon therapy in the past, owing to concerns about its side effects. She was unaware of the benefits of DAA treatment, probably due to communication difficulties caused by senile hearing loss. Consultation with an oral surgeon for an erosive form of OLP led her to receive antiviral therapy for hepatitis C. She achieved a sustained virologic response (SVR) following the DAA treatment, along with improvements in the signs and symptoms of OLP. Oral surgeons play an important role as gatekeepers in guiding untreated hepatitis patients toward appropriate treatment.